Pengembangan E-Modul Berbasis Inkuiri Terbimbing Terintegrasi Virtual Laboratory pada Materi Asam Basa Kelas XI SMA atau MA - Reni Oktarina; Andromeda Andromeda (Universitas Negeri Padang, 2021)
Acid and base are a chemical material that contains facts, concepts, principles and procedures. This research aims to produce an e-module based on guided inquiry integrated virtual laboratory on acid-base material which is valid and practical. The development model used is the 4-D model. The validity test of the e-module was carried out by experts, namely 2 UNP chemistry lecturers, 1 UNP educational technology lecturer and 2 chemistry teachers, while the practicality test was carried out by 2 chemistry teachers and 18 students of SMAN 3 South Solok. The research instrument used was a validity questionnaire and a practicality questionnaire. The results of the validity and practicality test were analysed using the Aiken V formula, which obtained an average validity test with the high validity category, and the practicality test by teachers and students with high practicality categories. The result of the analysis of the answer to the e-module obtained an average the correct answer of 91,07 percent on the key questions, 92,38 percent on the worksheets and 91,9 percent on the evaluation sheets. Based on the research result, it can be concluded that the acid-base e-module is valid and practical.